Analyzing the Sociodemographic and Psychological Factors Influencing the Intention to Consume Single-Use Plastics Among University Students: A Cross-Sectional Quantitative Study - Harahap, Alprida; Adi Antoni; Haslinah Ahmad; Anton J. Hadi; Nanda Masraini Daulay (Jurnal Teknokes, 2025)
The rising use of disposable plastics among Indonesian university students contributes to the growing problem of plastic waste, making it essential to understand the factors shaping their intentions to use single-use plastics. This research aims to determine the impact of sociodemographic factors (age, education level, and economic status) and psychological factors (subjective norms, emotional motivation, and beliefs) on the intention to use disposable plastic among university students. The study contributes by integrating the Theory of Planned Behaviour (TPB) and the Value-Belief-Norm (VBN) Theory to explain the intention to consume single-use plastics in the Indonesian context, identifying the belief variable as the most dominant factor influencing behavioral intention. The research employed a quantitative descriptive-analytical approach with a cross-sectional design, conducted from April to June 2024. A total of 125 respondents were selected using purposive sampling. Data were collected through questionnaires developed based on the TPB and VBN frameworks, then analyzed using descriptive statistical tests and multivariate logistic regression to identify significant predictors of behavioral intention. The results show that sociodemographic factors, age (p = 0.002), education level (p = 0.000), and economic status (p = 0.000), significantly influence the intention to consume disposable plastics. Likewise, psychological factors, subjective norms (p = 0.001), emotional motivation (p = 0.000), and beliefs (p = 0.000), also have a significant effect, with beliefs emerging as the most dominant factor (Exp(B) = 10.234). The study implies that efforts to reduce single-use plastic consumption among university students should focus on strengthening environmental education and transforming social norms to foster sustainable behaviors. Furthermore, future research with longitudinal designs and broader populations is recommended to enhance the generalizability of these findings.